The paddy innovation centre at Simpang Empat, Perlis - Abdul Jamil, Ahmad Faisal; Sanusi, Aliyah Nur Zafirah (IIUM Press, 2024)
The paddy industry is vital in Malaysia, contributing around 300,500 hectares to rice production. However, the sector requires improvements to achieve self-sufficiency in rice production. Currently, Malaysia relies on rice imports to meet national food security needs. Several issues affect rice production in Malaysia, with social issues being the most prominent, followed by environmental and economic concerns. Additional challenges includes lack of innovation in developing new paddy varieties and insufficient awareness and education regarding modern farming technologies and innovations in the paddy industry. Therefore, to ensure a secure future, the paddy innovation center aims to enhance the quality and quantity of local paddy production, by introducing innovations in the paddy industry and integrating the farming community into a collaborative laboratory environment with researchers. The center also offers educational and entertaining experience for the people. Consequently, the research output will be a fully developed innovation center that educates the community about the importance of the paddy industry and fosters collaboration between researchers and the community. This collaboration will facilitate knowledge exchange and practical demonstrations of innovations and technologies in paddy farming. Additionally, it aims to raise awareness and engagement among farming communities and attract the younger generation to participate in the process and improve the paddy industry in Malaysia.